A longitudinal study on caring behaviors of Italian nursing students. (May 2020) - Fenizia, Elisa; Navarini, Luca; Scollo, Sarah; Gambera, Angelo; Ciccozzi, Massimo
Abstract: Aim and objective: The aim of this study was to analyze the caring behavioral differences taking place over the nursing academic period. Background: Caring is a core value in nursing education and many of its features can be measured as specific behaviors. The Italian Caring Behaviors Inventory is a tested psychometric questionnaire, useful to this aim. The use of the questionnaire facilitates the student's self-reflection and awareness. Design: Descriptive longitudinal study. Method: The Italian Caring Behaviors Inventory questionnaire was filled out by 103 undergraduate nursing students at two Italian universities from May 2016 to May 2018 both during the second and the third year course. The questionnaire features 24 items with four caring factors: Factor 1 'Being with', Factor 2 'Doing with competence', Factor 3 'Responding to individual needs', Factor 4 'Providing effective care'. The Wilcoxon signed-rank test was used to assess differences between factors. Multiple regression analyses were conducted in order to evaluate variables associated with the increase or decrease of factors over time. Results: Results show a significant increase in Factor 2 during the selected period, which is positively associated with delta-Factor 1 and delta-Factor 3 and negatively associated with surgery clerkship during the third year of their course. Moreover, there is a significant decrease in Factor 3 between the second and third academic year and the variable positively associated to this decrease is the delta-Factor 4. Conclusions: One of the main risks of nursing education is an asymmetric impact in favour of doing at the expense of being. In this study, we demonstrated that nursing students reported an increase in instrumental caring and a decrease in expressive caring. These results suggest that a specific training in expressive caring in the third term could be a viable answer to this unmet need in nursing education.